Skeletal Muscle Changes Assessed by Preoperative Computed Tomography Images Can Predict the Long‐Term Prognosis of Stage III Colorectal Cancer. Issue 3 (13th December 2021) - Yokoi, Keigo; Tanaka, Toshimichi; Kojo, Ken; Miura, Hirohisa; Yamanashi, Takahiro; Sato, Takeo; Yamashita, Keishi; Kumamoto, Yusuke; Hiki, Naoki; Naitoh, Takeshi
Abstract: Background: Myopenia and myosteatosis are reported to be long‐term prognostic factors in patients with colorectal cancer (CRC). However, the established parameters are unsuitable for the Japanese population because their body composition is different from that of the Western population. Objective: We aimed to elucidate the effect of skeletal muscle changes among Japanese adults, measured using preoperative computed tomography (CT) as a prognostic factor in patients with stage III CRC. Patients: We retrospectively analyzed 341 patients diagnosed with stage III CRC. The cross‐sectional area (skeletal muscle index: SMI) and mean radiodensity of skeletal muscle (skeletal muscle radiodensity: SMR) were measured using preoperative CT. The optimal sex‐specific cutoff value, which was used to divide the patients according to the risk of recurrence, was set for SMI and SMR. Univariate and multivariate analysis were performed to determine the prognostic factors for recurrence‐free survival (RFS). Results: The cutoff values of SMI for men and women were set as 48.5 and 41.4, respectively, and those of SMR were 35.0 and 21.7, respectively. Univariate analysis identified low SMI and SMR in men and low SMR in women as the worst prognostic factors for RFS. Multivariate analysis identified low SMI in men and low SMR in women as independent poor prognostic factors for RFS (hazard ratio [HR] = 1.87, 95% confidence interval [CI], 1.08–3.47, P = .03 and HR = 2.49, CI, 1.21–4.95, P = .01). Conclusion: Low SMI in men and low SMR in women were the independent prognostic factors for patients with stage III CRC. Abstract : Low SMI in men and low SMR in women were the independent worse prognostic factors in stage III colorectal cancer.